Extracellular NM23 Protein as a Therapeutic Target for Hematologic Malignancies - Junko Okabe-Kado; Takashi Kasukabe; Yasuhiko Kaneko (Advances in Hematology)
An elevated serum level of NM23-H1 protein is a poor prognostic factor in patients with various hematologic malignancies. The extracellular NM23-H1 protein promotes the in vitro growth and survival of acute myelogenous leukemia (AML) cells and inversely inhibits the in vitro survival of normal peripheral blood monocytes in primary culture at concentrations equivalent to the levels found in the serum of AML patients. The growth and survival promoting activity to AML cells is associated with cytokine production and activation of mitogen-activated protein kinases (MAPKs) and signal transducers and activators of transcription (STAT) signaling pathways. Inhibitors specific for MAPK signaling pathways inhibit the growth/survival-promoting activity of NM23-H1. These findings indicate a novel biological action of extracellular NM23-H1 and its association with poor prognosis. These results suggest an important role of extracellular NM23-H1 in the malignant progression of leukemia and a potential therapeutic target for these malignancies.